2006
DOI: 10.5194/acp-6-4545-2006
|View full text |Cite
|
Sign up to set email alerts
|

Separation of emitted and photochemical formaldehyde in Mexico City using a statistical analysis and a new pair of gas-phase tracers

Abstract: Abstract. Photochemical pollution control strategies require an understanding of photochemical oxidation precursors, making it important to distinguish between primary and secondary sources of HCHO. Estimates for the relative strengths of primary and secondary sources of formaldehyde (HCHO) were obtained using a statistical regression analysis with time series data of carbon monoxide (CO) and glyoxal (CHOCHO) measured in the Mexico City Metropolitan Area (MCMA) during the spring of 2003. Differences between Ea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
157
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(174 citation statements)
references
References 33 publications
6
157
0
2
Order By: Relevance
“…Several previous studies in various urban areas (Anderson et al, 1996;Possanzini et al, 1996;Friedfeld et al, 2002;Possanzini et al, 2002;Rappenglück et al, 2005;Garcia et al, 2006) estimated contributions of primary emissions to the observed HCHO; up to 37% was estimated for the HGA (Friedfeld et al, 2002). The primary HCHO fraction originating from traffic emissions showed strong diurnal variation (Rappenglück et al, 2005;Garcia et al, 2006) with morning rush hour maxima (up to 100%) and midday minima (down to 20%) as insolation intensity reached a maximum.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Several previous studies in various urban areas (Anderson et al, 1996;Possanzini et al, 1996;Friedfeld et al, 2002;Possanzini et al, 2002;Rappenglück et al, 2005;Garcia et al, 2006) estimated contributions of primary emissions to the observed HCHO; up to 37% was estimated for the HGA (Friedfeld et al, 2002). The primary HCHO fraction originating from traffic emissions showed strong diurnal variation (Rappenglück et al, 2005;Garcia et al, 2006) with morning rush hour maxima (up to 100%) and midday minima (down to 20%) as insolation intensity reached a maximum.…”
Section: Introductionmentioning
confidence: 96%
“…Since CO is directly being emitted from combustion, CO has previously been used in urban studies to evaluate the traffic exhaust related HCHO emissions (Anderson et al, 1996;Possanzini et al, 1996;Friedfeld et al, 2002;Rappenglück et al, 2005;Garcia et al, 2006). Dynanometer studies showed that the emission ratio of HCHO/CO is typically 0.001-0.002 ppbv/ppbv for gasoline engine passenger cars, but can be 10× higher for diesel cars depending on driving conditions (Schmitz et al, 1999).…”
Section: Possible Contributions To Ambient Hcho Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This topic was further addressed in paper 4 (Garcia et al, 2006), which used ambient glyoxal concentrations, as novel tracer of photochemical activity, along with CO, an exhaust emissions tracer, to estimate that primary (vehicular) emissions were responsible for as much ambient HCHO near within the MCMA urban core as the well known photochemical secondary HCHO source. Paper 9 (Velasco et al, 2007) aggregated mobile laboratory real-time and canister sampled VOC measurements with similar data from a central fixed site to assess the concentration and spatial distributions, diurnal patterns and reactivities of ambient VOCs, allowing an insightful evaluation of the VOC emission inventories for the MCMA.…”
Section: Mcma-2002/2003 Data Analyses and Publicationsmentioning
confidence: 99%